2008
DOI: 10.1111/j.1600-0560.2007.00832.x
|View full text |Cite
|
Sign up to set email alerts
|

Bcl‐2, CD34 and CD10 expression in basaloid follicular hamartoma, vellus hair hamartoma and neurofollicular hamartoma demonstrate full follicular differentiation

Abstract: Generalized basaloid follicular hamartoma syndrome (GBFHS) is a rare, recently-described, autosomal-dominantly inherited disorder that presents with disseminated milia, palmoplantar pitting, hypotrichosis and basaloid follicular hamartomas (BFH). BFH is a benign adnexal tumor that resembles basal cell carcinoma (BCC). In this study, we report two cases of GBFHS and stain BFH, a vellus hair hamartoma (VHH) and a neurofollicular hamartoma (NH) with CD34, bcl-2 and CD10 to characterize and compare the staining pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 34 publications
1
29
0
2
Order By: Relevance
“…These findings are consistent with the histopathologic features of BFH. Moreover, immunohistochemical study indicated CD34 and CD10 positive fibroblasts and CD10 negative basal cells in the matrix, which also supports the diagnosis of BFH 8,9 . In the patient, there were localized plaque and nodules on the right face, and the lesions did not distribute along Blaschko’s lines.…”
Section: Discussionsupporting
confidence: 72%
“…These findings are consistent with the histopathologic features of BFH. Moreover, immunohistochemical study indicated CD34 and CD10 positive fibroblasts and CD10 negative basal cells in the matrix, which also supports the diagnosis of BFH 8,9 . In the patient, there were localized plaque and nodules on the right face, and the lesions did not distribute along Blaschko’s lines.…”
Section: Discussionsupporting
confidence: 72%
“…54,63,[65][66][67] A similar pattern of tumor expression in BCC and stromal expression in TE/TB has been proposed for CD34, but some reports have not found this stain diagnostically useful. 61,64,68,69 Although p75NTR is more likely to show diffuse expression in DTE than in mBCC, 70 a later study 71 demonstrated limited specificity, with diffuse expression in 36% of mBCC and 44% of microcystic adnexal carcinomas. In recent studies, strong and diffuse expression of PHLDA1 (TDAG51), a follicular stem-cell marker, has been shown to be highly specific for TE/TB, 53,55,72 although expression in micronodular BCC has been reported.…”
Section: Benign Hair-germ Tumors (Trichoepithelioma Andmentioning
confidence: 99%
“…The former is overwhelmingly BER-EP4 negative while the latter is diffusely positive. The stroma of BCC (including the fibroepithelioma of Pinkus variant) is CD34 negative but positive in BFH, 16 which feature it shares with other benign follicular tumors. Basal cell carcinoma expresses androgen receptors whereas BFH does not.…”
Section: Discussionmentioning
confidence: 98%
“…17 BCL-2 positivity is scattered throughout the lobules and cords of BCC but is restricted to the peripheral cells of the trabeculae constituting BFH. 16 Ki-67…”
Section: Discussionmentioning
confidence: 99%